TAMAN WISATA IMAN (TWI) SEBAGAI SARANA PEREKAT KERUKUNAN HIDUP BERAGAMA DI SITINJO KABUPATEN DAIRI SUMATERA UTARA - Girsang, Daud Candra; Isjoni, Isjoni; Tugiman, Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Interreligious harmony can be regarded as a social condition in which all religious groups can co-exist together without prejudice to their respective basic right to carry out their religious obligations. The interreligious harmony that is meant is to strive for the creation of a state where there is no internal conflict within each religious people, among different religious groups, among the followers of one religion and the followers of other religions, between religious people with the government. To maintain and improve the attitude of harmony, many of which provide solutions ranging from socialization by the government and educational tanyangan that exist in telivisi, but it takes real evidence that sangup be an example of the word harmony. In one area in Indonesia stands a place known as the Taman Wisata Iman (TWI) located in Sitinjo, North Sumatra. The park has an interesting concept of religious harmony, where in a garden is provided a place of worship for 5 different religions, namely Islam, Christianity, Catholicism, Hinduism and Buddhism. The existence of this park is able to maintain and also improve the attitude of harmony among religious communities in this area. The existence of this park is worth to serve as an example of real evidence to keep the harmony of religious communities in the area around us.Keywords : Religious Harmony, Taman Wisata Iman ,Community Sitinjo